Optimalisasi Keuntungan pada Usaha Komoditi Bunga Krisan di Kecamatan Cipanas, Kabupaten Cianjur (Optimizing the Profits of Chrysanthemum Commodities in Cipanas, Cianjur) - Wien Kuntari; Uding Sastrawan (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2013)
Many farmers are interested in planting chrysanthemums because of its beautiful colors. The allocation of land resources, raw materials, machinery, capital and labor which is now done by farmers, is relatively not able to meet the desired target. It demonstrates that the use of resources is not optimal and it will have an impact on the level of benefits received. The result of the data processing was: the Chrysanthemum production rate, based on the optimization results, illustrated that the recommended type of chrysanthemum to be produced was only the standard type, because it increased the revenue for companies. Company A produced 486.11 bunches of chrysanthemum for Rp 1,701,389 per growing season, company B produced 277.77 bunches for Rp 972,222 per growing season, company C produced 150 bunches for Rp 450,000 per growing season, and company D produced 250 bunches for Rp 750,000 per growing season. The resource or factor of production that was totally applied on the optimum condition was the green house land resources, which is a limiting resource; but other resources was excessive or not a limiting resource. The usage or availability of limiting resource could be improved to increase the profit of the company. The environmental changes can affect the company's revenue, to see how big the changes which didn’t change the optimal conditions were. It was generated by looking at the results of the sensitivity analysis. Sensitivity analysis of the objective coefficient value which was obtained for the standard type of chrysanthemum, the allowed increase in gross profit was infinity, while the allowed decrease in gross profit was when it approached the value of the gross profit.Keyword: chrysanthemum, primal analysis, dual analysis, sensitivity analysis